SOSIALISASI MANAJEMEN WIRAUSAHA BAGI PEMUDA KAMPUNG KEMANGI DALAM MEMPERTAHANKAN UMKM BATU BATA KAMPUNG KAMANGI DISTRIK TANAH MIRING - Florentina Blandina Parapaga; Maria Kaok (Musamus Devotion Journal, 2023)
UMKM in Kampung Kamangi face the problem of a lack of good entrepreneurial management skills. This has an impact on the low ability to produce, market and manage business finances. The problem is further complicated due to limited knowledge of access to capital, which has resulted in MSME actors borrowing business capital from brick collectors, which has an impact on controlling selling prices below market prices. This service activity aims to carry out an entrepreneurial management socialization activity, with lecture and discussion methods. The benefits achieved are an increase in understanding related to good entrepreneurial management and creating strong entrepreneurs, so that it can have an impact on the economy of the Kamangi village community.